Preparation, characterization and catalytic activity studies of organoruthenium‐supported polyoxotungstates on SBA‐15. (2nd October 2014) - Suo, Lin; Meng, Rui‐Qi; Zheng, Da‐Ming; Wu, Li‐Xin; Bi, Li‐Hua
<x xml:space="preserve">Abstract</x> Organoruthenium‐supported polyoxometalates [(RuC6H6)XW9O34]7− (XWRu; X = As, P) were selected as samples to study their catalytic activities towards the solvent‐free oxidation of n‐hexadecane. First of all, the XWRu were deposited on 3‐aminopropyltriethoxysilane‐modified SBA‐15 to prepare solid catalysts, which were characterized using powder X‐ray diffraction, nitrogen adsorption measurements, Fourier transform infrared reflectance spectroscopy and X‐ray photoelectron spectroscopy. Subsequently, their catalytic performances and stabilities were assessed through the oxidation of n‐hexadecane using air as the oxygen source without any additives and solvents, and the influences of the loading amount, catalyst amount, reaction time and reaction temperature on the catalytic activities were investigated. The results indicated the influence of the central heteroatoms X of XWRu on the catalytic activities. Copyright © 2014 John Wiley & Sons, Ltd.